1995
DOI: 10.1007/bf01001234
|View full text |Cite
|
Sign up to set email alerts
|

The quantity approach to financial integration: The Feldstein-Horioka criterion revisited

Abstract: The quantity approach to financial integration Lemmen, J.J.G.; Eijffinger, Sylvester

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
7
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
5
7
0
2
Order By: Relevance
“…The results show that this may be misleading if saving is not weakly exogenous for the parameters of the cointegration vector. 6 This result is consistent with the works ofMiller (1988),Lemmen and Eijfinger (1995) andSarno and Taylor (1998) who provide evidence that saving and investment are not cointegrated after an exogenously imposed break point coinciding with the end of the Bretton Woods system.…”
supporting
confidence: 93%
“…The results show that this may be misleading if saving is not weakly exogenous for the parameters of the cointegration vector. 6 This result is consistent with the works ofMiller (1988),Lemmen and Eijfinger (1995) andSarno and Taylor (1998) who provide evidence that saving and investment are not cointegrated after an exogenously imposed break point coinciding with the end of the Bretton Woods system.…”
supporting
confidence: 93%
“…In the first case the authors are led to confirm two ideas: the international mobility of the capital was very high for the period of the traditional gold standard; it was considerable less for the period of the Bretton-Woods agreements, with an increasing tendency after the abandonment of this regime (Hogendorn 1998, Bayoumi 1990, Blanchard and Giavazzi 2002; at the same time, the mobility of the capital for the less developed countries is always higher than that obtained for developed countries (Coakley et al 1999, Mamingi 1997, Chakrabarti 2006, Payne and Kumazawa 2006, Payne and Mohammadi 2006. Obviously there are results which contradict those (Lemmen andEijffinger 1998, Rocha andZerbini 2002) and Coakley et al (1999) support the assumption that a low value for the coefficient of retention can be simply the result of weak economic policy measures in response to external imbalances. Other authors, such as Pomfret (1998), defend the idea according to which the test of F-H is a reasonable measurement of the immobility of capital, but not of the mobility of capital.…”
Section: The Adaptation Of F-h Thesis To the Resultssupporting
confidence: 58%
“…And consequently, one must expect that the coefficient of retention of F-H (b) can have values far from unity. 5 From a more formal point of view, Lemmen and Eijffinger (1998) showed that the conditions required by F-H to evaluate a perfect integration are really leonine. It is consequently natural that one can arrive at different ideas on actual integration when other methods are used (Bayoumi 1990, Sachs 1981, Obstfeld 1986, Frankel 1991, Levy 1995, Frankel and MacArthur 1988, Popper 1990, Baxter and Crucini 1993, Bayoumi and MacDonald 1995, Goldberg et al 2003.…”
Section: Thesis Of Feldstein and Horioka And International Capital Momentioning
confidence: 99%
“…Equation (2) lies at the heart of the so-called "quantity approach" to the measurement of international financial integration (Lemmen and Eijffinger 1995). This approach originates from the study of Feldstein and Horioka (1980), who test the hypothesis β=1 in the cross-section regression…”
Section: Twin Deficits Modelmentioning
confidence: 99%